Rare-earth doped fluoride phosphate glasses: structural foundations of their luminescence properties. Issue 32 (2nd August 2017) - Galleani, Gustavo; Santagneli, Silvia Helena; Messaddeq, Younes; de Oliveira, Marcos; Eckert, Hellmut
Abstract : We report a detailed structural investigation of a series of fluoride–phosphate glasses with different phosphate/fluoride ratios in the system x Sr(PO3 )2 –(100 − x )[AlF3 –CaF2 –SrF2 –MgF2 ] with x = 5, 10, 20, 40. Abstract : We report a detailed structural investigation of a series of fluoride–phosphate glasses with different phosphate/fluoride ratios in the system x Sr(PO3 )2 –(100 − x )[AlF3 –CaF2 –SrF2 –MgF2 ] with x = 5, 10, 20, 40. Raman and multinuclear solid NMR spectroscopies confirm that the polyphosphate network structure is successively transformed to a structure dominated by Al–O–P linkages with increasing AlF3 content. Average numbers of Al–O–P linkages have been quantified by 27 Al/ 31 P NMR double-resonance techniques. The majority of the fluoride species are found in an alkaline earth metal/aluminum rich environment. The local environments for rare-earth ions have been characterized by EPR spectroscopy of Yb 3+ ion spin probes and by photoluminescence experiments on Eu 3+ dopant ions, including the 5 D0 → 7 F2 and 5 D0 → 7 F1 transition intensity ratio, the normalized phonon sideband intensities in the excitation spectra, and the lifetime of the 5 D0 excited state. The results indicate clear correlations between these parameters as a function of composition, and confirm that even at the highest fluoride levels, there is still some residual rare-earth phosphate coordination.